The relationship between teachers’ perceived sense of organizational trust and their organisational citizenship behaviors - Gökyer, Necmi (Sakarya University, 2017)
The aim of the study is to examine the relationship between the perceived sense of organizational trust and the organizational citizenship behaviors of teachers working in public elementary, econdary and high schools located in Elazığ and Bingöl. Participants were 564 teachers selected by the non-random sampling technique of purposive sampling. The results showed that male teachers have higher sense of organizational trust mean scores than females, and married teachers have higher sense of organizational trust mean scores than singles. A high, positive and significant relationship was detected between teachers’ organizational citizenship behaviours and the subfactors of volunteering, conscience, helpfulness, and sportsmanship. A moderate, positive and significant relationship was also found between organizational citizenship behaviors and organizational trust, trust for the principal, trust for teachers, trust for parents and for students. © The Turkish Online Journal of Educational Technology.
Keywords: Organizational citizenship behaviors; Organizational trust; Private and public school